Pengenaan Pajak Bumi dan Bangunan untuk Kawasan Perhutanan Sosial: Telaah Literatur - Susilawati, Hanik (Politeknik Keuangan Negara STAN, 2024)
This study aims to provide an alternative to the imposition of PBB for social forestry areas. Currently, the imposition of PBB in the forestry sector regulated by the DGT does not include this area in its taxation provisions. This condition gives opportunity for local governments to impose PBB on these areas located in production forests. Taxation alternatives were identified based on existing regulations, including laws, government regulations and ministerial regulations. Alternative regulations are then analyzed using Adam Smith's tax collection principles. Based on the analysis, it is known that all tax collection principles are met, except the principle of equality. The principle of equality may not be fulfilled due to the possibility of different tax rates for the same taxpayer on social forestry areas across districts/cities, due to differences in regulations on PBB imposition between regions. The anticipation is that local governments can coordinate for this condition and conduct a balance analysis to make the imposition fairer. As for the principles of certainty, convenience of payment, and economy, the suggested alternative has been fulfilled.